Broken Heart Syndrome; A Recurrent Presentation in a Teenager Female - Eltayeb, MBBS, Abdulrahman; Ogran, MD, Hassan; Eltayeb, MD, Abdalla (International Journal of Innovative Research in Medical Science, 2022)
Takotsubo syndrome (TTS) is a cause of heart failure with a wide range of clinical outcomes from mild to severe including, heart failure, arrhythmias and thromboembolic consequences. In its extreme forms, it can cause cardiogenic shock, strokes, and sudden cardiac death (SCD). This is a case report of a 21-year-old female with an unusual presentation of recurrent basal form of TTS (apical hyperkinesia with basal and mid segments akinesia), which was precipitated by recurrent painful crises of acute intermittent porphyria (AIP). AIP is an autosomal dominant disease resulting from a defect in porphobilinogen deaminase enzyme which is a part of the heme synthesis pathway. Acute attacks of AIP manifest mainly as episodes of abdominal pain, neuropathies and constipation. This case report highlights that TTS can occur in younger populations in contrast to what was classically described as the disease of post-menopausal women. It raises the awareness that TTS could be recurrent specially when there is proximity between the attacks.